2018
DOI: 10.1007/s00442-018-4243-y
|View full text |Cite
|
Sign up to set email alerts
|

Diverse effects of the common hippopotamus on plant communities and soil chemistry

Abstract: The ecological importance of the common hippopotamus (Hippopotamus amphibius) in aquatic ecosystems is becoming increasingly well known. These unique megaherbivores are also likely to have a formative influence on the terrestrial ecosystems in which they forage. In this study, we employed a novel exclosure design to exclude H. amphibius from experimental plots on near-river grasslands. Our three-year implementation of this experiment revealed a substantial influence of H. amphibius removal on both plant commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 59 publications
0
30
0
Order By: Relevance
“…Cattle, hippopotamuses and grazing tortoises share key functional similarities, they prefer highly palatable grasses with high bulk density to maximize intake of nutritious food per bite. McCauley et al [68] showed that a mixture of herbivores (including cattle and hippopotamuses) and removal of hippopotamuses on grazing lawns in East Africa similarly impacted grassland diversity and structure, suggesting some functional equivalence between hippopotamuses and livestock. The replacement of one grazer with another is unlikely to have substantially reshaped diversity where an obligate grazing flora already existed.…”
Section: Discussionmentioning
confidence: 99%
“…Cattle, hippopotamuses and grazing tortoises share key functional similarities, they prefer highly palatable grasses with high bulk density to maximize intake of nutritious food per bite. McCauley et al [68] showed that a mixture of herbivores (including cattle and hippopotamuses) and removal of hippopotamuses on grazing lawns in East Africa similarly impacted grassland diversity and structure, suggesting some functional equivalence between hippopotamuses and livestock. The replacement of one grazer with another is unlikely to have substantially reshaped diversity where an obligate grazing flora already existed.…”
Section: Discussionmentioning
confidence: 99%
“…This could potentially explain why H. amphibius used many of the available habitats less than expected. Floodplains are a key resource for H. amphibius because they are able to maintain grazing lawns with short-cropped, green foliose, an important resource for H. amphibius 3,26,42 , even at the peak of the dry season (Fig. 1b).…”
Section: Discussionmentioning
confidence: 99%
“…In African savannas, the common hippopotamus ( Hippopotamus amphibius ) is an important ecosystem engineer because it shapes the physical structure of ecosystems 1 , vegetation communities 2,3 , and biogeochemical cycling 4,5 . These effects are detectable in both aquatic and terrestrial ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…For example, these large grazers directly change the plant communities with respect to grass height and abundance and indirectly affect the abundance and diversity of aquatic animal species (McCauley et al, 2018; Stears et al, 2018). They could also influence the soil and watershed chemistry as well as silicon cycling between these two systems (McCauley et al, 2018; Schoelynck et al, 2019; Stears et al, 2018). Unfortunately, this megaherbivore population has undergone a dramatic decrease in number as a result of illegal hunting and habitat degradation (Lewison & Pluháček, 2017).…”
Section: Introductionmentioning
confidence: 99%